2005
DOI: 10.1292/jvms.67.1253
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Transforming Growth Factor-.BETA.1 in Feline Chronic Renal Failure

Abstract: ABSTRACT. Transforming growth factor-β1 (TGF-β1), an inflammatory cytokine, plays a role in tissue fibrosis, such as glomerular sclerosis and tubulointerstitial fibrosis of the kidneys. In the present study, the urinary TGF-β1 level of cats diagnosed with chronic renal failure (CRF) was measured to investigate its relationship to the pathogenesis of feline CRF. Urinary TGF-β1 levels (TGF-β1/creatinine ratio) were significantly increased compared with healthy controls, whereas serum levels of TGF-β1 were not. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 16 publications
2
34
3
5
Order By: Relevance
“…It is reported a TGF-β 1 mean concentration of 21.48 ± 8.948 ng/mL in serum samples taken from 12 cats [44]. This concentration was similar to the concentrations found in the supernatants of both PC but higher than the plasma TGF-β 1 concentration in this study.…”
Section: Discussionsupporting
confidence: 87%
“…It is reported a TGF-β 1 mean concentration of 21.48 ± 8.948 ng/mL in serum samples taken from 12 cats [44]. This concentration was similar to the concentrations found in the supernatants of both PC but higher than the plasma TGF-β 1 concentration in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Feline analytes were measured with feline-specific kits (IFNγ, TNFα, IL-6, IL-8, and IL-10: Duosets; R&D Systems, Minneapolis, MN, USA) or feline-validated kits (TGFβ1: multispecies TGF-β1 (ThermoFisher Scientific) [41]; VEGF: human QuantiKine Kit (R&D) [42, 43]; and PGE 2 : competitive ELISA (Enzo Life Sciences, Farmingdale, NY, USA) [44, 45]). Human TGFβ1, VEGF, IFNγ, TNFα (QuantiKine), PGE 2 , (competitive ELISA kit), IL-6, IL-8, and IL-10 (DuoSets) were all purchased from R&D. All ELISA samples were read on a Synergy HTMulti-Mode microplate reader with Gen5 software (Biotek, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…107,108 However, conflicting studies evaluating active rather than total urinary TGF-β1 found no significant difference between non-azotemic geriatric cats, nonazotemic cats that progressed to develop azotemia and azotemic cats. However, there was a trend towards increasing active urinary TGF-β in cats that developed azotemia and were monitored longitudinally.…”
Section: Evidence Of Fibrosis In Feline Chronic Kidney Diseasementioning
confidence: 99%